Your Insides - Cole, Joanna (New York : The Putnam & Grosset Group, 1992)
Examines the different parts of the body and how they worked, including the muscles, digestive organs, and lungs.
Keywords: Body, Human-Juvenile literature; Human physiology-Juvenile literature; Body, Human; Human physiology